1993
DOI: 10.1079/bjn19930024
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and tissue concentrations of α-tocopherol during vitamin E depletion in sheep

Abstract: To determine the relationship between plasma and tissue a-tocopherol concentrations during vitamin E depletion, weaned lambs were placed on a vitamin E-deficient diet for 0, 1, 2, 4, 8 and 12 weeks. aTocopherol was measured in plasma, erythrocytes, liver, adrenal, adipose tissue, three different skeletal muscles and heart muscle. The a-tocopherol concentration in plasma fell at the same rate as the atocopherol concentration in skeletal muscles, heart muscle, adrenal and adipose tissue. The a-tocopherol concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
5
20
1
Order By: Relevance
“…These results agree with those reported by Asghar et al (1991) for pigs 5 to 14 wk of age and with those reported by Fry et al (1993) for sheep. Values of CK activity in plasma in the present experiment ranged from 973 to 2,593 IU, except at 14 d of age.…”
Section: Discussionsupporting
confidence: 96%
“…These results agree with those reported by Asghar et al (1991) for pigs 5 to 14 wk of age and with those reported by Fry et al (1993) for sheep. Values of CK activity in plasma in the present experiment ranged from 973 to 2,593 IU, except at 14 d of age.…”
Section: Discussionsupporting
confidence: 96%
“…This threshold concentration can be easily reached by supplementing lambs with 275IU -tocopherol acetate/kg of feed (daily requirement being 440mg-tocopherol acetate/sheep.day) for a period of 3 to 4 weeks. Because the depletion of vitamin E in the muscle can occur rapidly (Fry et al, 1993), it is important that the supply of -tocopherol be continual for this period, up until…”
Section: Discussionmentioning
confidence: 99%
“…Lambs were sourced in summer from a commercial farm where they grazed dry pasture supplemented with lupin grain at the rate of 600g/lamb/day, conditions in which tissue vitamin E levels are rapidly depleted (Fry, Smith, McGrath, Speijers & Allen, 1993). Initial plasma measurements, confirmed that all animals entering the experiment were deficient or close to deficient in vitamin E (< 0.5mg/L; (Menzies, Langs, Boermans, Martin & McNally, 2004)).…”
Section: Lambs and Dietary Treatmentsmentioning
confidence: 99%
“…As a fat-soluble vitamin, a proportion of vitamin E is stored in adipose tissue; together with liver and muscle, adipose tissue may account for more than 90% of vitamin E in the body (Debier and Larondelle, 2005). Tissue uptake (Toutain et al, 1995) and depletion (Fry et al, 1993;Hidiroglou et al, 2003) studies have shown that adipose tissue acquires vitamin E more avidly and is depleted at a similar rate to muscle. In the current study and those of Capper et al (2005) and Merrell (1999) the concentrate feed offered to the sheep was intended to result in some mobilisation of adipose tissue during late pregnancy.…”
Section: Discussionmentioning
confidence: 99%